(untitled) (Journal of Engineering, 2012)
This study investigated the ability of using crushed glass solid wastes in water filtration by using a pilot plant, constructed in Al-Wathba water treatment plant in Baghdad. Different depths and different grain sizes of crushed glass were used as mono and dual media with sand and porcelaniate in the filtration process. The mathematical model by Tufenkji and Elimelech was used to evaluate the initial collection efficiency η of these filters. The results indicated that the collection efficiency varied inversely with the filtration rate. For the mono media filters the theoretical ηth values were more than the practical values ηprac calculated from the experimental work. In the glass filter ηprac was obtained by multiplying ηth by a factor 0.945 where this factor was 0.714 for the sand filter. All the dual filters showed that ηth was less than ηprac. Whereas the dual filter 35cm porcelanite and 35cm glass showed the highest collection efficiency. To obtain ηprac in the dual filter glass and sand, ηth is multiplied by 1.374, as for the dual filters porcelanite and glass the factor was 1.168 and 1.204.